Handling Cases of Bullying Practices in The School Environment in Terms of Criminal Law - Dores, Dedi; Mubarok, M. Khusni; Setiawan, Hery; Kumala, Milka; Khilmi, Muhammad (International Journal of Sustainable Law, 2024)
This research aims to find out what are the backgrounds of bulliying, law enforcement for perpetrators, protection for victims and how to find solutions so that bulliying cases do not mushroom in places that should be a place of knowledge. The research method used is normative research method using regulatory approach. Legal protection for victims of bullying crimes is regulated in Article 76C of the Child Protection Law No. 35 of 2014. This article contains content that prohibits violence against children. Legal protection against the perpetrators of bullying, where the perpetrator also has rights that are his rights, protection can be achieved by prioritizing differences in efforts to overcome the problem of bullying and by overriding criminal penalties, if diversion does not find an agreement, then specifically the perpetrators of child crimes are tried taking into account the principles contained in Law Number 11 of 2012 concerning the Juvenile Justice System. Crime prevention efforts can be divided into penal prevention (criminal law) and non eanal prevention (other than criminal law).